GE_GERICHTE P/18651/2014 vom 20. Januar 2020 - GE Cour de justice (2020)
QUALITÉ POUR AGIR ET RECOURIR;INFRACTIONS EN MATIÈRE DE LP;COMPÉTENCE RATIONE LOCI;ESCROQUERIE | cpp.115; cpp.118; cp.146; cp.158; cp.164; cp.305; cp.307; cp.322; cpp.426